OFC/NFOEC 2007 - 2007 Conference on Optical Fiber Communication and the National Fiber Optic Engineers Conference 2007
DOI: 10.1109/ofc.2007.4348644
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of very high negative chromatic dispersion dual-core photonic crystal fiber

Abstract: This paper reports the experimental drawing fabrication of very large negative chromatic dispersion dual-core photonic crystal fiber. The fabricated fiber has a peak chromatic dispersion value of -820 ps/(nm km).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Although we can see that our results has some deviations with the measured chromatic dispersion these are in better agreement with that calculated in [16].…”
Section: Calculation Of Effective Refractive Indexsupporting
confidence: 88%
See 2 more Smart Citations
“…Although we can see that our results has some deviations with the measured chromatic dispersion these are in better agreement with that calculated in [16].…”
Section: Calculation Of Effective Refractive Indexsupporting
confidence: 88%
“…5(b) with solid line, whereas one calculated in [16] with dashed line and experimentally measured with dash-dot line. The fiber has narrow bandwidth of negative dispersion because the negative dispersion occurs only at wavelength around the phase matching wavelength.…”
Section: Calculation Of Effective Refractive Indexmentioning
confidence: 97%
See 1 more Smart Citation
“…Yang et al in Tsinghua University designed a kind of dualcore structured PCF (DC-PCF), shown in Fig. 4, and it was successfully fabricated by Fiberhome Telecommunication Technologies Co., Ltd. Figure 5 shows that the peak dispersion value of this PCF is -666.2 ps/(nm$km) [38,39]. The position of the dispersion peak is at the wavelength of 1586 nm, which has a shift from the designed peak position.…”
Section: Dispersion Compensation Pcf and Dispersion Compensationmentioning
confidence: 99%